Low-carbon economic operation of energy hub integrated with linearization model and nodal energy-carbon price - Ma, Siyuan (2024)
Energy hub has positive significance in absorbing renewable energy, improving energy utilization efficiency and reducing carbon emissions. Considering both linearization energy hub model and nodal integrated energy-carbon price, a low-carbon economic operation model of energy hub is constructed by taking advantage of the bi-level optimization structure. First, in order to simplify the modeling procedures and improve the solving efficiency, reversibility judgment criteria and linearization processes in energy hub modeling are improved. Then, a nodal integrated energy-carbon pricing strategy is proposed and calculated according to flow tracing method and carbon emission flow method. Additionally, the bi-level optimization model and solution procedure are presented to obtain the optimal operating states of energy hubs. At last, for the simulation results, the characteristics and the influence of nodal price on energy consumption behaviors of energy hubs are analyzed, the proposed model is effective to reduce the carbon emissions and operating costs.